2022
DOI: 10.1177/00178969221079587
|View full text |Cite
|
Sign up to set email alerts
|

Effective strategies for testicular torsion education in adolescents: A qualitative study in educational environments

Abstract: Objective: In the context of testicular torsion, research demonstrates a delay from the onset of testicular pain to attending hospital in adolescents, leading to high rates of testicular loss. This is due to a lack of knowledge about this condition. In this study, we aimed to investigate the methods adolescents and their parents felt would be effective in testicular torsion education. Design: Qualitative semi-structured interviews and focus group workshops were used to generate ideas and opinions regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is evident that the general awareness of TT is deficient, with most individuals unaware that TT can occur, potentially leading to testicular loss. This deficiency in awareness appears to be true for all levels of society and educational ability, as in our patients' families [5,8,[15][16][17][18]. In comparison to families whose children underwent surgery for other reasons, our families demonstrated erratic behavior when confronted with the possibility of testicular loss due to delay.…”
Section: Discussionmentioning
confidence: 68%
“…It is evident that the general awareness of TT is deficient, with most individuals unaware that TT can occur, potentially leading to testicular loss. This deficiency in awareness appears to be true for all levels of society and educational ability, as in our patients' families [5,8,[15][16][17][18]. In comparison to families whose children underwent surgery for other reasons, our families demonstrated erratic behavior when confronted with the possibility of testicular loss due to delay.…”
Section: Discussionmentioning
confidence: 68%
“…A focus group of males aged 11 to 18 found that second to teaching in their school classrooms, social media was reported to be the most effective method of disseminating information about testicular torsion. 9 While many studies discuss the importance of education in reducing rates of orchiectomy, we were unable to find literature that discusses the use of social media as a tool to disseminate information about testicular torsion. 10 Patients and families are increasingly seeking healthcare information online, and are turning to platforms such as Instagram and Facebook more than ever before, with as many as 92.4% of parents stating that it is important for physicians to have an online social media presence.…”
Section: Discussionmentioning
confidence: 96%
“…In the study of MacDonald et al (2022), the opinions of adolescents and their parents about a possible health education for testicular disorders were taken. The qualitative ndings obtained show that participants support school-based health education.…”
Section: Introductionmentioning
confidence: 99%